Fetal frontal cortex transplanted to injured motor/sensory cortex of adult rats. I. NADPH-diaphorase neurons - Gonzalez, MF (J Neurosci, 1987)
Fetal frontal cortex from 18-d-old embryonic rat brain was transplanted into cavities of juvenile host motor/sensory cortex. Two to seven months later, sections were reacted for NADPH-diaphorase (NADPH-d) enzyme histochemistry. NADPH-d-positive neurons survived in 11 of 13 grafts. All but one of the transplants had reduced numbers of these neurons, although in 3 transplants the reductions were moderate and not statistically significant. The distribution and morphology of NADPH-d neurons within most grafts was comparable to that of NADPH-d neurons in normal host cortex. At the margin of the 2 transplants with no NADPH-d neuronal perikarya, NADPH-d fibers crossed from host to transplant as far as a millimeter into the transplant, and on rare occasions, the host neurons that gave rise to these fibers were identified. This suggests that host-transplant interactions are possible. One transplant had an abnormally large number of NADPH-d-positive neurons and fibers, possibly due to selective survival of these neurons. The data reported here for NADPH-d in cortical transplants may also apply to neuropeptide Y (NPY), since nearly all neocortical NPY neurons also contain NADPH-d.